REPRESENTATION OF BEAUTY IN THE WARDAH ADVERTISEMENT “IMPACTFUL BEAUTY FOR THE GREATER GOOD” (2024) - Fatmawati, Efa; Rofik, Abdur; Musliadi, Musliadi (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2024)
This research was conducted to analyze the representation of beauty in the Wardah advertisement "Impactful Beauty for the Greater Good" (2024). There are three problem formulations in this research. First, how are beauty signs represented in the Wardah advertisement "Impactful Beauty for the Greater Good" Second, How are beauty objects represented in the Wardah advertisement "Impactful Beauty for the Greater Good" And third, How are beauty interpretants represented in the Wardah advertisement "Impactful Beauty for the Greater Good". The researchers used qualitative methods to study this problem. The theory and approach that researchers use is Charles Sanders Pierce's Semiotics theory. The results of this research show that based on the Beauty Signs, Beauty Objects and Beauty Interpretants contained in the Wardah advertisement "Impactful Beauty for the Greater Good" it can be concluded that Beauty does not have to be seen from physical appearance which has images which are in principle related to all the organs of a woman's body from head to toe, but real beauty is beauty from within such as positive traits and morals as well as usefulness in goodness.